Pentafsiran al-Quran dalam Bidang Akidah Menurut Dawam Rahardjo: INTERPRETATION OF THE QUR'AN IN AQIDAH MATTERS ACCORDING TO DAWAM RAHARDJO - Rino Riyaldi,; Bambang Irawan,; Wan Muhammad Fariq,; M.Kafrawi, (Advances in Humanities and Contemporary Studies, 2021)
AbstrakDawam Rahardjo adalah seorang tokoh modenis dan pemikir Muslim di Indonesia yang juga terlibat dalam bidang penafsiran. Beliau telah memberikan sumbangan terhadap pemikiran Islam dan bidang penafsiran al-Qur’an, walaubagaimanapun pemikiran dan penafsirannya didakwa sesetengah pihak telah menyeleweng dan menimbulkan kontroversi. Kajian ini bertujuan memperkenalkan Dawam Rahardjo dan mengenal pasti penafsirannya terhadap al-Quran khusus di bidang akidah. Kajian ini merupakan kajian kualitatif yang menggunakan pendekatan kaedah analisis dokumen dalam proses pengumpulan data. Analisis data dilakukan dengan menumpukan kajian terhadap karya-karya yang dihasilkannya berkenaan al-Qur’an. Pemerolehan data dari karya-karyanya amat diperlukan untuk membantu memahami dan menganalisis pemikirannya dalam mentafsirkan ayat-ayat al-Qur’an. Data-data yang dikumpulkan dianalisis melalui pendekatan deskriptif, ekspanatori dan komperatif. Hasil kajian mendapati bahawa penafsiran al-Quran Dawam Rahardjo dalam bidang akidah menyalahi kaedah dan bercanggah dengan pendapat majoriti ulama, serta menimbulkan kontroversi. Penafsiran beliau dalam bidang akidah iaitu tentang makna Islam, syafa’at, kebebasan beragama dan kesempurnaan al-Qur’an. Kajian ini memberi implikasi penting kepada umat Islam Indonesia khususnya dan Nusantara secara umumnya. Melalui kajian ini umat Islam akan mendapatkan penjelasan dan penerangan terhadap isu kontroversi yang timbul daripada penyimpangan penafsiran Dawam Rahardjo. Selain itu, kajian ini juga merupakan satu kajian penting terhadap bidang tafsir demi menjelaskan pemahaman yang sebenar terhadap al-Qur’an.Kata kunci: Penafsiran; al-Qur’an; Akidah; Dawam Rahardjo.  AbstractDawam Rahardjo is a modernist figure and Muslim thinker from Indonesia who is also involved in the field of exegesis. He has given contribution to Islamic thought and the field of interpretation of the Qur’an, however, his interpretation and thought is claimed by some people to have deviated, thus sparking controversy. This study intends to introduce Dawam Raharjo and identify his interpretation of the Qur'an specifically in the aqidah matters. This study is qualitative using document analysis approach in the process of collecting data. Analysis of the data is done by concentrating this study on works that are produced with regards to the Qur’an. The acquisition of the data from the works is much needed to help clarify and analyse his thought in interpreting the Qur’anic verses. The collected data is analysed through descriptive, explanatory and comparative approaches. The outcome of this study is that Dawam Raharjo’s interpretation in aqidah matters mostly contradicts the method and opinions of majority of traditional Muslim scholars, apart from inciting controversy. His interpretation in aqidah matters is about the meaning of Islam, intercession, freedom of choosing religion and perfection of the Qur’an. This findings bring an important implication to the Muslim ummah in Indonesia specifically and Nusantara generally. Through this study, the Muslim ummah would gain the clarification and explanation to controversial issues arising from the deviated interpretation of Dawam Raharjo. Besides, this study is also considered significant in the field of exegesis devoted to expounding the true understanding of the Qur’an.  Keywords: Interpretation; Qur’an; Aqidah; Dawam Rahardjo.